Linguistic Appeals in Political Discourse: A Multimodal Discourse Analysis of 2023 Presidential Election Billboards and Posters in Nigeria - Peter Oyewole Makinde; Barnabas Fiyinfoluwa Adejumo (Yayasan Visi Intan Permata, 2024)
In the wake of the campaign for the 2023 Presidential election in Nigeria, several political parties were shown to rely on linguistic appeals as a tool for political discourse in their campaign. This has sparked a paradigm shift in the role of linguistics in political discourse. This study examines the linguistic strategies used in political discourse to appeal to voters through a multimodal discourse analysis of campaign posters and billboards. The study utilises a qualitative research design. Data for the study were collected from Vanguard Newspapers and Punch Newspapers. Using Kress and Van Leeuwen's multimodal framework, the study explores how political candidates' use of language, visuals, slogans, colours and other meaning-making resources enhance political discourse, as evident in their posters and billboards. Findings from the study provide valuable insights into the power of linguistics in political campaigns and the potential for language to shape public perception and influence election outcomes. Thus, the findings underscore the significance of verbal and visual multimodal modes, illustrating their effectiveness in conveying nuanced meanings associated with diverse political parties and candidates. The posters and billboards showcase party affiliations and employ diverse elements to strategically communicate messages to the public, showcasing the intricate interplay between linguistic and visual components in political discourse.